Groundwater Management Through Participatory Rural Appraisal (Pra) And Modelling Approach In Briand Tract: Groundwater Management in the Barind Tract - Khan, Md Sydur Rahman; Hossain, Md Jahid; Haque, M Aminul (Journal of the Sylhet Agricultural University, 2025)
Groundwater is a vital source for drinking and agricultural purposes in Chapainawabganj district. The scarcity of water in surface water bodies causes high dependency on groundwater resources. Despite being a riverine country, Bangladesh faces growing concerns over its water resources, as revealed in a comprehensive study across 45 unions in five upazilas of Chapainawabganj district. The aim of this paper is to investigate the aquifer system and groundwater level up to union level of Chapainawabganj district. Existing historical data has been collected from BWDB, BMD and other relevant agencies. Rainfall data has been collected for the duration of 1985 to 2023. Existing hydro-geological data that includes groundwater level, lithologs and aquifer properties has been collected from available secondary sources. In addition, to fulfill the data gap, a comprehensive field investigation program has been conducted that includes exploratory drilling at 19 locations. Borelog data indicates that the aquifer system mostly falls under two physiographic units: Barind Tract and Ganges Flood plain. Through participatory rural appraisal (PRA), local communities shared critical insights into the state of water resources, complemented by hydrological investigations of both surface and groundwater. The area holds 5,184 surface water bodies, including 4,944 ponds and 240 beels. Groundwater table depths vary annually from 3.0 to 27.5 meters, with recharge rates ranging between 193 and 727 mm per year. Transmissivity values range from 89 to 4,648 m²/day, while storage coefficients for the first aquifer vary from 0.0000748 to 0.1781. Water scarcity levels differ across the region, with 11 unions experiencing very low scarcity, 14 facing moderate, 10 high, and another 10 enduring very high scarcity. Notably, very high-water stress affects 1 union in Chapainawabganj Sadar, 5 in Gomostapur, and 4 in Nachol, while high stress is observed in 3 unions each in Chapainawabganj Sadar and Gomostapur, and 4 in Shibganj. Alarmingly, excessive groundwater extraction for agriculture-particularly in Nachol and Gomostapur-has led to significant declines in groundwater levels, signaling urgent need for sustainable water management practices. J. Sylhet Agril. Univ. 12(1): 132-141, 2025